A Systematic Overview of the Measurement Properties of the Chronic Respiratory Questionnaire - Yves Lacasse; Eric Wong; Gordon Guyatt (Canadian Respiratory Journal)
BACKGROUND: Assessment of health-related quality of life (HRQL) of patients with chronic lung disease has become an important aspect of many clinical investigations. The authors examined the measurement properties of a disease-specific HRQL questionnaire, the Chronic Respiratory Questionnaire (CRQ), when used by independent investigators in clinical trials and observational studies.